Direct and indirect evidence of size-selective grazing on pelagic bacteria by freshwater nanoflagellates - Simek, K; Chrzanowski, T H (Applied and environmental microbiology, 1992)
Size-selective grazing of three heterotrophic nanoflagellates (with cell sizes of 21, 44, and 66 mum) isolated from Lake Arlington, Texas was examined by using a natural mixture of fluorescence labelled lake bacteria. Sizes of ingested bacteria in food vacuoles were directly measured. Larger bacterial cells were ingested at a frequency much higher than that at which they occurred in the assemblage, indicating preferential flagellate grazing on the larger size classes within the lake bacterioplankton. Water samples were collected biweekly from June through September, 1989, fractionated by filtration, and incubated for 40 h at in situ temperatures. The average bacterial size was always larger in water which was passed through 1-mum-pore-size filters (1-mum-filtered water) (which was predator free) than in 5-mum-filtered water (which contained flagellates only) or in unfiltered water (in which all bacterivores were present). The increase of bacterial-cell size in 1-mum-filtered water was caused by a shift in the size structure of the bacterioplankton population. Larger cells became more abundant in the absence of flagellate grazing.